2007
DOI: 10.1002/ibd.20134
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study using PET/CT as a novel, noninvasive assessment of disease activity in inflammatory bowel disease

Abstract: We found that PET activity correlated well with active inflammation in both UC and CD, suggesting that this may be a noninvasive method of identifying disease activity in patients with inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(46 citation statements)
references
References 14 publications
0
42
0
4
Order By: Relevance
“…It is also unclear in which clinical context PET/CT might be a reasonable tool to study human IBD. In ulcerative colitis, the correlation of disease activity and PET/CT has been shown to be as high as 95% (26). Because the activity of ulcerative colitis is limited to the colon, and the mucosal damage can be easily determined by partial colonoscopy, the benefit for the diagnosis of ulcerative colitis is currently rather limited.…”
Section: Discussionmentioning
confidence: 99%
“…It is also unclear in which clinical context PET/CT might be a reasonable tool to study human IBD. In ulcerative colitis, the correlation of disease activity and PET/CT has been shown to be as high as 95% (26). Because the activity of ulcerative colitis is limited to the colon, and the mucosal damage can be easily determined by partial colonoscopy, the benefit for the diagnosis of ulcerative colitis is currently rather limited.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that 18 F-FDG PET and PET/CT in adult and pediatric patients, compared with standard endoscopy, histology, radiography, and small bowel imaging, are useful for identifying active IBD (15,(23)(24)(25)(26)(27)(28). Sensitivities for this purpose have been reported to range from 54% to 98%, with specificities from 55% to 81% (15,(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Initial animal and human data suggest that the noninvasive imaging technique using 18 F-FDG and PET may help for identifying gastrointestinal inflammation (15,(23)(24)(25)(26)(27)(28). Combined PET/CT scanners offer more precise lesion characterization and localization (26,27).…”
mentioning
confidence: 99%
“…Animal experiments provide evidence supporting the hypothesis that FDG signal is produced by uptake in inflammatory cell infiltrates in gut tissue [10][11][12] . Previous studies in Crohn's patients suggest that 18 F-FDG PET has a high sensitivity and moderately high specificity in demonstrating bowel segments with active Crohn's disease 25,21,31,32 . Moreover good correlations between PET measures and endoscopic and histo-pathological reference standards have been shown [10][11][12]33 .…”
Section: Discussionmentioning
confidence: 99%
“…A VOI of at least 40cm 3 was created inside the liver parenchyma and the mean SUV (LivSUVMEAN) was recorded ( Figure 1A). In keeping with published literature, the resulting LivSUVMEAN was used as a threshold above which GI signal was classified as abnormal 25,21 . The entire fused 3-D sequence was thus adjusted to exclude signal of intensity lower than LivSUVMEAN ( Figure 1B).…”
Section: Mri Scanningmentioning
confidence: 99%